Technical means as sources of evidence in cases of administrative offenses: under the prism of observing human rights and freedoms - M. A. Sambor (Law and Safety)
The article is devoted to the study of the legal regulation of the use of technical means related to the implementation of video recording, photography and filming by subjects of public administration, in particular, those authorized to draw up protocols on administrative offenses by officials. The research is carried out on the basis of strict observance of human rights and freedoms, as fundamental principles of civil society and a democratic state, which should determine the powers, their use, and therefore the behavior of subjects of public administration during the use of technical means of videography, photography and filmmaking. It is argued that no socially significant goal may be the basis for limiting or depriving a person of his or her rights and freedoms, including the right to privacy, in any form. It is reasoned that the use of relevant technical means in administrative delict proceedings has a number of features and a number of imperatives, the violation of which leads to the inadmissibility of relevant evidence. In particular, it is emphasized that the installation of video surveillance systems in public (public) places must necessarily be accompanied by the installation of appropriate posters, informational signs indicating the implementation of video surveillance and the implementation of video recording, photography and filming, and therefore the preservation and accumulation of such information about person and the possibility of using it for the appropriate purposes and with the appropriate purpose.